Peran Anggota DPRD dalam Pengajuan dan Pembahasan RAPERDA Menjadi PERDA (Studi di DPRD Kota Blitar) - Divi Agustina (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2014)
Abstract: Role of Local Council Members in Submission dan Discussion of Local Regulation Draft (RAPERDA) into Local Regulation (PERDA) (Study in Blitar City Local Council). Members of Local Council in carrying out its functions in the field of regulation granted the right to submit a RAPERDA into PERDA. Cconstitutional change must be able to drive productivity of Blitar City Local Council members to use their rights in the submission and discussion of regulation draft be pro PERDAs with people. The results of this study indicate that: (1) Members of Local Council have a good role in both the submission and discussion of draft regulation becomes PERDA, (2) In the implementation the mechanism of RAPERDA’s submission and discussion that proposed by members of council to be PERDA dominated by members of council, and (3) Factors that influence members of Local Council in lawmaking in Blitar City, are : (a) Until now the government has not Blitar Local Regulation Program yet, (b) Lack of budget funds provided by Blitar Government in submission dan discussion of proposed RAPERDA to be PERDA by council member, (c) The ability of legislators who are less competent in the field of the submission and discussion of draft regulation becomes PERDA, and (d) Agenda’s of Council members that too much. Keywords : Role of Local Council Members, Local Regulation, Blitar City. Abstrak: Peran Anggota DPRD Dalam Pengajuan dan Pembahasan RAPERDA Menjadi PERDA (Studi Di DPRD Kota Blitar). Anggota DPRD dalam menjalankan fungsinya di bidang legislasi diberikan hak untuk mengajukan RAPERDA menjadi PERDA. Perubahan konstitusional tersebut seharusnya mampu mendorong produktivitas anggota DPRD Kota Blitar dalam menggunakan hak yang dimilikinya tersebut dalam pengajuan dan pembahasan RAPERDA menjadi PERDA yang pro rakyat. Hasil penelitian ini menunjukkan bahwa: (1) Anggota DPRD memiliki peran baik dalam pengajuan maupun pembahasan RAPERDA menjadi PERDA, (2) Dalam pelaksanaannya, mekanisme pengajuan dan pembahasan RAPERDA yang diusulkan anggota DPRD menjadi PERDA didominasi oleh anggota DPRD dan (3) Faktor–faktor yang mempengaruhi anggota DPRD dalam penyusunan PERDA di Kota Blitar antara lain: (a) Pemerintah Kota Blitar belum memiliki Program Legislasi Daerah, (b) Minimnya anggaran dana yang disediakan Pemerintah Kota Blitar dalam bidang pengajuan dan pembahasan RAPERDA yang diusulkan anggota DPRD untuk menjadi PERDA, (c) Kemampuan anggota DPRD yang kurang kompeten dalam bidang pengajuan dan pembahasan RAPERDA menjadi PERDA, dan (d) Agenda anggota DPRD yang padat. Kata Kunci: Peran Anggota DPRD, Peraturan Daerah, Kota Blitar.